Analisis Peran Hukum Kesehatan dalam Menjamin Keadilan Pelayanan Medis di Indonesia - Rian Prayudi Saputra; Ahmad Riandi; Ahmad Khuzri; M. Rizki (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
Health law is an essential discipline that governs the rights and obligations of healthcare providers and patients. This article explores the role of health law in ensuring justice and quality in medical services in Indonesia. Using a qualitative method, the study analyzes regulations, cases, and legal frameworks relevant to medical practices. The research findings indicate that stronger legal awareness and enforcement can prevent malpractice and strengthen trust in the healthcare system.